PROFIL PENJUAL JAGUNG BAKAR (Studi Sektor Informal Pada Malam Hari di Jalan Air Hitam Kota Pekanbaru) - Simbolon, Risky Martiana Br; Yusuf, Yusmar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted at Jalan Air Hitam Pekanbaru City with the aim of obtaining information about Corn Seller Profile . Problems to be studied is as follows (1) How does the outpouring of family labor in the sale of corn? (2) How does the social relationships in a corn merchant activity? The title of this research is "Seller Profile Corn (Study of Informal sector At Night In Pekanbaru Jalan Air Hitam)" the purpose of the research is as follows: To find out how the outpouring of family labor in the sale of corn. To determine social relations in a corn merchant activity. In order to facilitate the authors to analyze the actions roasted corn sellers in Jalan Air Hitam village Labuh Western New Sekaki Umbrella District of Pekanbaru, using the theories related to this research: social capital theory, functional structure and social action. This research is qualitative phenomenon because of its shape, Informants in this study are those writers who considered good choice in providing the information needed writers. In this study the technique determination / determination informants used by the author in the research is purposive sampling technique with a sampling technique based on the desired goals of the writer. Data collection techniques using observation, interviews and documentation. Having done this study, The results of this research note that the seller sells roasted corn in a way not true and there are relationships in aktvitas selling grilled corn on Jalan Air Hitam.Keywords: Informal Sector, Seller Corn, Night